2020
DOI: 10.1097/dss.0000000000002018
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Outcomes of Nasal Burow's Grafts With Interdomal Sutures After Mohs Micrographic Surgery

Abstract: BACKGROUND Post-Mohs reconstruction of distal nasal defects is challenging. Many repair options exist, each with advantages and disadvantages. Utilization of a Burow's graft in combination with manipulation of the underlying nasal cartilages with interdomal sutures is an underreported yet effective repair option. OBJECTIVE To present the authors' experience with Burow's grafts facilitated by interdomal sutures for repair of nasal defects after Mohs micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Although this technique is well-known to plastic surgeons and otolaryngologists who perform rhinoplasties, there are limited data in the dermatology literature. 3,5 Previous reports of this neoadjuvant technique followed by Burow's full-thickness skin grafts demonstrate low complication rates and a reduced need for revision due to preservation of symmetry and overall long-term cosmesis. 3 To the authors' knowledge, the use of this adjuvant technique with E-W flaps has not been previously described in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this technique is well-known to plastic surgeons and otolaryngologists who perform rhinoplasties, there are limited data in the dermatology literature. 3,5 Previous reports of this neoadjuvant technique followed by Burow's full-thickness skin grafts demonstrate low complication rates and a reduced need for revision due to preservation of symmetry and overall long-term cosmesis. 3 To the authors' knowledge, the use of this adjuvant technique with E-W flaps has not been previously described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Although historically used as a rhinoplasty technique, the interdomal suture (IDS) has been described as a simple adjuvant to Burrow's grafting for preservation of nasal tip projection after MMS. 3 The authors have found the IDS similarly useful and effective when paired with E-W advancement flaps.…”
mentioning
confidence: 98%
“…4 The ultimate goal of defect reconstruction is to maximize the esthetic outcome with excellent texture and color matching while maintaining function of the airway. 5 Full-thickness skin grafts (FTSGs) are one of the most efficient and commonly used closure options for defects on the nasal ala. 6 Donor sites for FTSGs are selected based on tissue match, which includes color, thickness, actinic damage, and sebaceous quality of the skin. Common donor sites for nasal repair include the preauricular, postauricular, supraclavicular, clavicular, conchal bowl, and glabellar areas.…”
mentioning
confidence: 99%
“…4 The ultimate goal of defect reconstruction is to maximize the esthetic outcome with excellent texture and color matching while maintaining function of the airway. 5 Full-thickness skin grafts (FTSGs) are one of the most efficient and commonly used closure options for defects on the nasal ala. 6…”
mentioning
confidence: 99%